The likely impact of climate change on the biodiversity of Italian forests - Borghetti, M.; La Mantia, T.; Menozzi, P.; Piotti, a (Forest@ - Rivista di Selvicoltura ed Ecologia Forestale, 2012)
Keywords: 2012; 245-250; 9; Adaptation; biodiversità delle foreste italiane; Biodiversity; borghetti m; citation; climate change; climatico sulla; contents; FOREST; http; impact; it; Italy; la mantia t; menozzi p; online 2012-11-19; piotti a; probabili impatti del cambiamento; sisef; url; www

Viscoelastic impact characterisation of solid sports balls used in the Irish sport of Hurling - Collins, Fiachra; Brabazon, Dermot; Moran, Kieran (Sports Engineering, 2011)
In recent years, variability in behaviour of the sliotar, a small leather-bound ball used in the Irish sport of hurling, has become evident in championship matches. The inconsistency in performance was attributed to the range of constructions and material compositions of currently approved ball types. With a view to adopting a standard core, a new methodology has been commissioned to assess the dynamic impact behaviour of approved sliotar cores. In this paper, the relationship between the dynamic stiffness and the coefﬁcient of restitution is presented with regard to material properties, ball construction and viscoelastic strain and strain-rate dependencies. The modern polymer ball types were shown to exhibit strain-rate sensitivity, while the performance of the traditional multi-compositional ball types exhibited lesser strain-rate dependence. The traditional balls types were shown to be up to 2.5 times stiffer than the modern ball types, with this ﬁnding having implications for ball energy dissipation.
Keywords: Ball types; compression (voyant); deformation; impact; stifness

Conservation strategy of a nature reserve in Mediterranean ecosystems: the effects of protection from grazing on biodiversity - Verdú, J R; Crespo, M B; Galante, Eduardo (Biodiversity and Conservation, 2000)
Protection of natural areas has caused the elimination of traditional grazing activity on many occasions. As a result, in Mediterranean ecosystems a loss of biodiversity is usually related to a decrease of grassland and grassland–bush mosaic areas. In order to establish relationships between land use and the relative importance of each type of habitat in terms of species richness and endemicity, the Font Roja Natural Park in Alicante Province (SE Iberian Peninsula) was studied. Four sites were selected representing the four different existing habitats: a wooded area (holm-oak forest), a dense shrubland, a dense grassland, and a grassland–shrubland mosaic area. In each site, the species composition of vegetation and dung beetle fauna were analysed. The results showed that the highest diversity and endemicity, for plants and beetles, were concentrated in the dense grasslands and the grassland–shrubland mosaic. Thus, controlled grazing activity of sheep and goats which maintained a diverse variegated landscape would favour the historical sustenance of the biodiversity of Mediterranean ecosystems, as that would allow a remarkable diversity of habitats with higher conservation levels of existing species richness and endemicity. Therefore, we propose a reintroduction of traditional grazing of sheep and goats throughout ecological, cultural and economical measures, which would include guidelines and regulations, set out to boost an integrated rural policy.
Keywords: dung beetles; endemicity; impact; management; vascular plants

Conservation strategy of a nature reserve in Mediterranean ecosystems: the effects of protection from grazing on biodiversity - Verdú, J. R.; Crespo, M. B.; Galante, Eduardo (Biodiversity and Conservation, 2000)
Protection of natural areas has caused the elimination of traditional grazing activity on many occasions. As a result, in Mediterranean ecosystems a loss of biodiversity is usually related to a decrease of grassland and grassland–bush mosaic areas. In order to establish relationships between land use and the relative importance of each type of habitat in terms of species richness and endemicity, the Font Roja Natural Park in Alicante Province (SE Iberian Peninsula) was studied. Four sites were selected representing the four different existing habitats: a wooded area (holm-oak forest), a dense shrubland, a dense grassland, and a grassland–shrubland mosaic area. In each site, the species composition of vegetation and dung beetle fauna were analysed. The results showed that the highest diversity and endemicity, for plants and beetles, were concentrated in the dense grasslands and the grassland–shrubland mosaic. Thus, controlled grazing activity of sheep and goats which maintained a diverse variegated landscape would favour the historical sustenance of the biodiversity of Mediterranean ecosystems, as that would allow a remarkable diversity of habitats with higher conservation levels of existing species richness and endemicity. Therefore, we propose a reintroduction of traditional grazing of sheep and goats throughout ecological, cultural and economical measures, which would include guidelines and regulations, set out to boost an integrated rural policy.
Keywords: dung beetles; endemicity; impact; management; vascular plants

INFLUENCIA DE LAS COBERTURAS DE ENCINAS , Quercus ilex subsp. ballota , EN LA ROTURA DE LOS PERFILES TERMICOS VERTICALES - Escudero Garcia, J C; Cabezas Fernández, J; Lavado Contador, F (CONGRESO FORESTAL ESPAÑOL - Lourizán 1.993, 1993)
Vegetation cover acts intensely on vertical temperature profiles, breaking up their structure. For the particular case of holm oak parkland (dehesas) forests systems, these will affect the vertical temperature gradient by modifying it more or less sharply as a function funtamenta1ly of the height and characteristics of the canopy, the density of trees ánd of foliage load. The study was carried in Cheles (Badajoz), and consisted in periodic measurements of the temperature variations in the profile. The results show quantitatively the influence of arboreal systems on the vertical structure of air and soil temperatures. A characterlzation is thereJore given of the thermal impact that intense pruning and destruction of holm oaks have on the vertical profIle, especially that of he soil.
Keywords: gradients; impact; Quercus ilex; Temperature

INFLUENCIA DE LAS COBERTURAS DE ENCINAS , Quercus ilex subsp. ballota , EN LA ROTURA DE LOS PERFILES TERMICOS VERTICALES - Escudero Garcia, J. C.; Cabezas Fernández, J.; Lavado Contador, F. (CONGRESO FORESTAL ESPAÑOL - Lourizán 1.993, 1993)
Vegetation cover acts intensely on vertical temperature profiles, breaking up their structure. For the particular case of holm oak parkland (dehesas) forests systems, these will affect the vertical temperature gradient by modifying it more or less sharply as a function funtamenta1ly of the height and characteristics of the canopy, the density of trees ánd of foliage load. The study was carried in Cheles (Badajoz), and consisted in periodic measurements of the temperature variations in the profile. The results show quantitatively the influence of arboreal systems on the vertical structure of air and soil temperatures. A characterlzation is thereJore given of the thermal impact that intense pruning and destruction of holm oaks have on the vertical profIle, especially that of he soil.
The following values have no corresponding Zotero field: periodical: CONGRESO FORESTAL ESPAÑOL - Lourizán 1.993
Keywords: gradients; impact; Quercus ilex; Temperature